Penerapan Konsep UML Dalam Perancangan Sistem Manajemen Kependudukan RW 022, Kelurahan Kebalen - Asshafa, Zaima Syarifa; Voutama, Apriade (INFORMAL: Informatics Journal, 2024)
Population data is something that really needs to be maintained and managed well. Using the old method of recording population data manually carries a fairly high risk of losing that data. The use of a computerized system is an option that can be taken for more effective and efficient management of population data. Therefore, it is necessary to design a population management system to design a population data management system so that it is more structured in a computerized manner. UML is used as an object-oriented system design method and is also a tool to support system development. With this system, the work of collecting population data will be easier and the data stored will also be safer because it uses integrated and computerized storage. This system also makes it easier for residents to handle administration or obtain information online without having to go directly to the management. This system design is based on a mobile application so that it can be accessed anytime and anywhere.